MULTIDISCIPLINARY DESIGN OPTIMIZATION OF TURBINE STAGE BASED ON IMPROVED BI-LEVEL INTEGRATED SYSTEM SYNTHESIS - ZHANG LiZhang; YIN ZeYong; MI Dong; QIAN ZhengMing; JIA ZhiGang (Jixie qiangdu)
To improve the optimization efficiency of turbine stage optimization,an improved optimization strategy based on Bi-level integrated system synthesis（ BLISS2000） procedure to the multidisciplinary design optimization（ MDO） of turbine stage was proposed. The key idea in this approach is to keep the basic algorithm structure of BLISS2000,cancel the process to generate approximation models,and use variable complexity method（ VCM） which in the aerodynamic analysis. The approach was evaluated and validated by a turbine blade optimization problem. The results were similar as those in standard strategy,but the optimization efficiency increased by 2. 75 times.